Effects of social anxiety on static and dynamic balance task assessment in older women - Orcioli-Silva, Diego [UNESP]; Pasman, Elizabeth P.; Gobbi, Lilian T.B. [UNESP]; Beauchamp, Mark R.; Carpenter, Mark G. (Elsevier, 2021)
Background: Social anxiety caused by the presence of an evaluator can impair balance performance in older women. However, it is unknown whether co-performing balance tasks with a partner mitigates this effect. Research question: Does the presence of a partner mitigate the effect of social anxiety on static and dynamic balance assessment in older women? Methods: Twenty-one older women (mean age 66.5 (SD = 5.2) years) performed nine balance tasks under three conditions: (a) Alone (no evaluator present); (b) Evaluator (male evaluator present); (c) Partner (evaluator + performing tasks in parallel with partner). Participants were split into two groups post-hoc: Affected (n = 10) and Unaffected (n = 11), based on their emotional response to the presence of the evaluator (increased self-reported anxiety and fear). Results: The affected group took a longer time to complete tandem walking with eyes open in the Evaluator vs. Alone condition, but not in the Partner condition. Both groups increased anterior-posterior trunk angular velocity during tandem walking with eyes closed in the Evaluator vs. Alone condition, but not in the Partner condition. Significance: Social anxiety impairs the balance performance of older women, particularly in those most affected by the evaluator, and during more dynamic modified gait tasks that challenge balance while walking. However, co-performing balance tasks with a partner reduced the effects of social anxiety, suggesting that social support may help to mitigate some of the potential ‘white coat’ effects experienced during clinical balance assessments.
Keywords: Aging; Anxious; Postural control; Social support; White coat